Quality Assurance System Of Learning Process In University - Ilham Fahmi; Iqbal Amar Muzaki (At-Tarbiyat, 2021)
This research aims to comprehensively examine the quality assurance system of learning processes in universities that focuses on the study of how universities manage the quality of learning processes, such as student learning needs, lecturer capacity, curriculum, learning facilities and financing in terms of seven quality elements namely quality philosophy, quality standards, quality policy, quality structures, quality processes, quality control cycles and quality assessments so that they form an alignment in conducting quality learning processes. The method used is a qualitative method with a case study approach. The results show that the quality assurance system of the learning process held at the university as a whole has not demonstrated the quality of the quality standards set by reviewing how institutions implement quality assurance systems to manage the quality of learning components. This research recommends the need for benchmarking and mentoring in the implementation of the quality assurance system of the learning process at university.